Cesium Carbonate Promoted Direct Arylation of Hydroxylamines and Oximes with Diaryliodonium Salts. Issue 31 (24th September 2014) - Yang, Yang; Wu, Xunshen; Han, Jianwei; Mao, Song; Qian, Xiaofei; Wang, Limin
Abstract: A transition‐metal‐free approach for the arylation of hydroxylamines and oximes with diaryliodonium salts was developed. The reaction proceeded smoothly at room temperature in the presence of cesium carbonate. As a result, a wide range of N ‐ and O ‐arylated hydroxylamines were synthesized in good to excellent yields (45–98 %). Abstract : An efficient method for the transition‐metal‐free arylation of hydroxylamines and oximes with diaryliodonium salts is described. A range of N ‐arylhydroxylamines with various aryl substituents that would be useful in the preparation of valuable chemicals are obtained in good to excellent yields. Cbz = benzyloxycarbonyl, Boc = tert ‐butoxycarbonyl, TBDMS = tert ‐butyldimethylsilyl, TBDPS = tert ‐butyldiphenylsilyl, Bn = benzyl, Tf = trifluoromethylsulfonyl.